Analysis of Nonlinear Narrative Structure in Building Dramatic Scenes in Jatuh Cinta Seperti di Film-Film - Oktora Candra Andika; Donie Fadjar Kurniawan, SS, M.Si., M.Hum (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
This study discusses how non-linear narrative structure is used to construct dramatic scenes in the film Jatuh Cinta Seperti di Film-Film. The purpose of this study is to analyze how the non-linear narrative structure contributes to four dramatic elements: conflict, suspense, curiosity, and surprise. This research uses a qualitative descriptive method to examine each scene in detail. The data were analyzed using narrative analysis techniques, including plot, time sequence, characters, conflict, goal, setting, and theme. The findings show that 27 scenes in the film display a non-linear narrative pattern, where scenes are arranged non-chronologically and often blend reality with imagination. This narrative approach effectively creates dramatic tension and emotional depth throughout the film. The presence of interconnected dramatic elements in each act strengthens the overall narrative and drives the story forward with emotional resonance.